Tax Smoothing in a Financially Repressed Economy : Evidence from India - Cashin, Paul.; Olekalns, Nilss; Sahay, Ratna (Washington, D.C. : International Monetary Fund, 1998)
India has a long history of running fiscal deficits. Two broad considerations motivate a government to run a deficit: tax smoothing and tax tilting. This paper tests a version of Barro's tax-smoothing model, using Indian data for the period 1951-52 to 1996-97. The empirical results indicate that the central government of India has tax-smoothed, while the regional governments of India have not. The paper also finds evidence of tax tilting, reflected in financial repression, which has led to the accumulation of excessive public liabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet